KECERNAAN NEUTRAL DETERGEN FIBER (NDF), ACID DETERGENT FIBER (ADF) DAN HEMISELULOSA HIJAUAN PAKAN SECARA IN VITRO - Isnaini Nurkhasanah; Limbang Kustiawan Nuswantara; Marry Christiyanto; Eko Pangestu (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2020)
This study aims to determine the effect of various types of forage on the fiber qualty for goat. The experimental design used was a randomized complete block design (RCBD) consisting of 7 treatment types of forage feed ingredients with 3 block rumens. The treatment was T1: indigofera leaves, T2: insulin leaves, T3: jambu biji leaves, T4: melinjo leaves, T5: rambutan leaves, T6: singkong leaves and T7: waru leaves. The results showed that the effect types of forage on NDF, ADF and hemicellulose digestibility was significantly different (P<0,5). The highest digestibility value of NDF is Indigofera leaves (61,48% dan 50,42%). The highest digestibility value of hemicellulase is Singkong leaves (74,21%).